Kecemasan dapat Mempengaruhi Kualitas Tidur - Teguh Rizal Aurora; Eka Hendryanny; Adjat R Rasjad (Bandung Conference Series: Medical Science, 2023)
Abstract. Anxiety is a situation of individual feelings when facing a situation that is considered to be self-threatening. New students have the opportunity to experience anxiety. Medical students are more prone to experiencing psychological anxiety than students of other majors. Medical students are considered to have high stressors, experiencing more pressure and tension. If this happens to students it will disrupt academic activities and cause a decrease in academic achievement. This study aims to determine the level of anxiety and sleep quality of students at the Faculty of Medicine level I, Bandung Islamic University for the 2021/2022 Academic Year and to analyze the relationship between these two factors. This research method used an analytic cross-sectional study with a simple random sampling technique. The samples obtained were 71 students and then crossed the anxiety data and sleep quality of the research subjects. Based on the cross-tabulation results, it was found that more students had very severe anxiety levels of 62% and more had poor sleep quality of 98.6%. Based on the results of the Spearman test, a significance value of 0.001 (<0.05) was obtained with a correlation coefficient of 0.400 which indicates that there is a moderate/sufficient relationship between anxiety levels and sleep quality in Level I Students of the Faculty of Medicine, Islamic University of Bandung, Academic Year 2021/2022. Anxiety in a person can cause stress hormones to interact with the brain and body so that it affects the quality of sleep. Keywords: Anxiety Level, Sleep Quality Abstrak. Kecemasan merupakan situasi perasaan individu ketika menghadapi situasi yang dianggap mengancam diri sendiri. Mahasiswa baru memiliki kesempatan untuk mengalami kecemasan. Mahasiswa kedokteran lebih rentan mengalami kecemasan psikologis dibandingkan mahasiswa jurusan lain. Mahasiswa kedokteran dianggap memiliki stressor yang tinggi, lebih banyak mengalami tekanan dan ketegangan. Jika hal ini terjadi pada siswa maka akan mengganggu kegiatan akademik dan menyebabkan penurunan prestasi akademik. Penelitian ini bertujuan untuk mengetahui tingkat kecemasan dan kualitas tidur mahasiswa Fakultas Kedokteran tingkat I Universitas Islam Bandung Tahun Akademik 2021/2022 dan menganalisis hubungan antara kedua faktor tersebut. Metode penelitian ini menggunakan studi cross-sectional analitik dengan teknik simple random sampling. Sampel yang diperoleh sebanyak 71 siswa kemudian disilangkan data kecemasan dan kualitas tidur subjek penelitian. Berdasarkan hasil tabulasi silang, ditemukan lebih banyak mahasiswa yang memiliki tingkat kecemasan sangat berat sebanyak 62% dan lebih banyak lagi yang memiliki kualitas tidur buruk sebanyak 98,6%. Berdasarkan hasil uji Spearman diperoleh nilai signifikansi sebesar 0,001 (<0,05) dengan koefisien korelasi sebesar 0,400 yang menunjukkan bahwa terdapat hubungan sedang/cukup antara tingkat kecemasan dengan kualitas tidur pada Mahasiswa Tingkat I Fakultas Ilmu Budaya. Kedokteran, Universitas Islam Bandung, Tahun Akademik 2021/2022. Kecemasan pada seseorang dapat menyebabkan hormon stres berinteraksi dengan otak dan tubuh sehingga mempengaruhi kualitas tidur. Kata kunci: Kualitas Tidur, Tingkat Kecemasan